Natural frequencies of axisymmetric vibrations of thin hyperbolic circular plates with clamped edges - Jaroszewicz, Jerzy (Zielona Góra: Uniwersytet Zielonogórski)
A free vibration analysis of homogeneous and isotropic circular thin plates with nonlinear thickness variation and clamped edges is considered. The limited independent solutions of differential Euler equation were expanded in the power series based on the properties of integral equations. The analytical frequency equations as power series were obtained using the method of successive approximations.
Keywords: circular plates; power series; clamped edge